Предмет: Алгебра,
автор: dashakh29987
1) 4ab+8b+3a+6=(4ad+8b) + (3a +6) =4b (a+2) + ... ;
2) a²b + 2c² - abc - 2ac = abc + 2c² = (a²b-abc)+(2c²-2ac) = ab (a-c) + 2c (c-a)=... .
Приложения:
Ответы
Автор ответа:
1
Ответ:
1) 4b (a + 2) + 3 (a + 2) = (4b + 3) (a + 2)
2) ab (a - c) + 2c (c - a) = ab (a - c) - 2c (a - c) = (ab - 2c) (a - c)
Объяснение:
dashakh29987:
Благодарю)
Похожие вопросы
Предмет: Окружающий мир,
автор: Аноним
Предмет: Русский язык,
автор: Аник21
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: Аноним